Sports. - Publications International, Ltd. (Lincolnwood, Ill. : Publications International, 1992)
Trivia about a wide range of international sports and sporting events, both historical and contemporary.
At head of title: Encyclopædia Britannica.
Includes index.
0
Keywords: Sports; Sports